Neuroborreliosis: the Guillain-Barré mimicker. (25th June 2015) - Tyagi, Niharika; Maheswaran, Tim; Wimalaratna, Sunil
Abstract : A 34-year-old woman presented to the medical admissions unit with progressive ascending weakness of her limbs and areflexia. Diagnosis of Guillain-Barré syndrome was suspected and she was started on intravenous immunoglobulins. Owing to a poor initial response, further exploratory history revealed travel to the New Forest and a possible tick bite; subsequent investigations confirmed positive serology for antibodies against Borrelia. The patient's weakness improved with intravenous ceftriaxone for neuroborreliosis, a manifestation of Lyme disease. With inpatient neurorehabilitation, she made good recovery and was able to mobilise with a stick from being completely bed bound 6 weeks after completion of her antibiotics.